Inventarisasi Tanaman Dengan Famili Araceae Di Villa Oemah Kajoe Lembang, Jawa Barat - Cahya, Cindy Alidya; Dinanti, Dara; Supriyatna, Ateng (Jurnal Ilmu Pertanian dan Perkebunan, 2023)
The diversity of flora and fauna in Indonesia is due to its tropical climate. The Araceae family is a very abundant flora with taro plant forms. Not only on land, Araceae also live in aquatic and epiphytes. Although abundant, data in several regions in Indonesia regarding Araceae is still lacking. Therefore, an inventory of plants is needed to fill in the gaps in the data using a purposive sampling method. There are several common characteristics possessed by plants in the Araceae group, such as chordate and sagitate leaf shapes. Further identification is needed to know the species and its benefits